E-Health: Current status and future trends - Demiris, George (IOS, 2013)
In this publication, e-health is defined as the use of advanced telecommunications such as the Internet, portable and other sophisticated devices, advanced networks and new design approaches aiming to support healthcare delivery and education. Thus, e-health refers to a fundamental redesign of healthcare processes based on the use and integration of electronic communication at all levels. It aims to lead to patient empowerment which describes the transition from a passive role where the patient is the recipient of care services to an active role where the patient is informed, has choices and is involved in the decision-making process. e-Health has the potential to improve efficiency on a global level when patients cross national boundaries to seek treatment in other countries and to enable medical facilities and services across countries to be linked and accessible to citizens. Discussion topics focus on the use of mobile technologies in healthcare, “smart home” technologies, telemedicine applications that cross national borders, transatlantic collaborations in bioinformatics and the use of the Internet in healthcare. Furthermore, legislative efforts and ethical concerns associated with the diffusion of e-health are discussed and policies in the EU and the US reviewed and compared